Problematika Hukum Keluarga Islam di Indonesia - Holan Riadi (LP3M STITNU AL HIKMAH MOJOKERTO, 2021)
In Indonesia, in an effort to maintain the actualization of family law, two major efforts have been carried out. Each social structure should develop its own legal system that is appropriate The problem of the relationship between social structure and law in Indonesia is of sufficient importance to be discussed, among others, to meet quite practical needs, for example in the framework of making and implementing effective laws, especially in the application of Islamic family law. in Indonesia. The purpose of this study is to explain the problems of Islamic family law in Indonesia. The method in this study uses a qualitative method with the type of descriptive analytic research. The results of this study indicate that the Islamic legal system in Indonesia has the same and equal position as other legal systems that exist in Indonesia, namely customary law and western law. The application and enforcement of Islamic law in Indonesia can be incorporated into national law, either through positive Islamic law or through Islamic legal values ​​that apply to all citizens. Both are influenced by political will that will shape the politics of legislation.